GSK‐3β regulates the synaptic expression of NMDA receptors via phosphorylation of phosphatidylinositol 4 kinase type IIα. (27th June 2020) - Amici, Mascia; Lee, Yeseul; Pope, Robert J. P.; Bradley, Clarrisa A.; Cole, Adam; Collingridge, Graham L.
Abstract: Deregulation of GSK‐3β is strongly implicated in a variety of serious brain conditions, such as Alzheimer disease, bipolar disorder and schizophrenia. To understand how GSK‐3β becomes dysregulated in these conditions, it is important to understand its physiological functions in the central nervous system. In this context, GSK‐3β plays a role in the induction of NMDA receptor‐dependent long‐term depression (LTD) and several substrates for GSK‐3β have been identified in this form of synaptic plasticity, including KLC‐2, PSD‐95 and tau. Stabilization of NMDA receptors at synapses has also been shown to involve GSK‐3β, but the substrates involved are currently unknown. Recent work has identified phosphatidylinositol 4 kinase type IIα (PI4KIIα) as a neuronal GSK‐3β substrate that can potentially regulate the surface expression of AMPA receptors. In the present study, we investigated the synaptic role of PI4KIIα in organotypic rat hippocampal slices. We found that knockdown of PI4KIIα has no effect on synaptic AMPA receptor‐mediated synaptic transmission but substantially reduces NMDA receptor‐mediated synaptic transmission. Furthermore, the ability of the selective GSK‐3 inhibitor, CT99021, to reduce the amplitude of NMDA receptor‐mediated currents was occluded in shRNA‐PI4KIIα transfected neurons. The effects of knocking down PI4KIIα were fully rescued by a shRNA‐resistant wild‐type construct, but not by a mutant construct that cannot be phosphorylated by GSK‐3β. These data suggest that GSK‐3β phosphorylates PI4KIIα to stabilize NMDA receptors at the synapse. Abstract : GSK3β phosphorylates PI4KII⍺ to stabilize synaptic NMDA receptors. .